Размещение и численность сурка степного (Marmota bobac Müll) в Ворошиловградской области - Сахно, И.И. (Вестник зоологии, 1972)
Location of M. bobac Müll colonies is mentioned and the quantity of the species in each colony is determined. The presenon of 67 colonies is established. Altogether about 19 thousand marmots inhabit the region. Their further dispersion is possible over the territory of northern areas up to the line Kovalevka- Nizhnepokrovka - Novoidar - Shiroky. The problem is set on the expediency lo regulation of the M. bobac Müll quantily.